AN EMPIRICAL RESEARCH ON FACTORS INFLUENCING CUSTOMER SATISFACTION AND BEHAVIORAL INTENTION TO REPURCHASE TOWARDS FAST FOOD RESTAURANT IN DHAKA, BANGLADESH - Mumtaz, Syeda Karishma; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The purpose of this research is to investigate the factors influencing customer satisfaction and behavioral intention to repurchase of customers towards KFC restaurant in Dhaka, Bangladesh. Empirical testing is conducted to deduce the result of this research. Data were collected from 450 respondents who have/had dining experience at KFC restaurant Dhaka, Bangladesh by using self-administered questionnaire. Multiple Linear regression (MLR) method was used for analysis and SPSS software was used to interpret the result. The researcher used judgement, quota, and convenience sampling to deduce the target population and location. It was revealed from the study that service quality in terms of tangible, reliability, responsiveness, assurance, and empathy has no significant influence on customer satisfaction. Perceived value in terms of hedonic and utilitarian value, price, food quality, physical environment quality has significant influence on customer satisfaction. Utilitarian value is a better predictor of customer satisfaction because of high beta value. Price, customer satisfaction and perceived value has significant influence on behavioral intention to repurchase. Customer satisfaction is a better predictor of behavioral intention to repurchase because of high beta value.